2014
DOI: 10.2478/acph-2014-0034
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of physicians, nurses and pharmacists concerning the development of clinical pharmacy activities in a university hospital

Abstract: A. Čufar et al.: Attitudes of physicians, nurses and pharmacists concerning the development of clinical pharmacy activities in a university hospital, Acta Pharm. 64 (2014) 447-461.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…While the lowest average score was for the statement that describes the clinical pharmacist as an authoritative figure with the power to switch similar medications without consulting the physician in necessary cases (2.035), which is also not surprising, mainly because of the blame culture that usually holds the physician accountable for any adverse events, and so they tend to be protective of their prescriptions, and it is unlikely for the pharmacist to take such responsibility. This is, to a certain degree, similar to one of the findings of a study conducted in Ljubljana, Slovenia, where most physicians did not expect pharmacists to have the authority to interchange similar medications without consulting them first (12) . Most participants were fairly positive about the clinical pharmacists' participation in the daily medical rounds (average score = 3.195), and even more so about clinical pharmacists' availability for consultation (average score = 3.37), which can imply that, in most cases, shortage of interventions is not necessarily due to lack of interaction, and this is contrary to the results of another study conducted in Baghdad were 91.5% of the participants reported rarely interacting with pharmacists (7) .…”
Section: Discussionsupporting
confidence: 84%
“…While the lowest average score was for the statement that describes the clinical pharmacist as an authoritative figure with the power to switch similar medications without consulting the physician in necessary cases (2.035), which is also not surprising, mainly because of the blame culture that usually holds the physician accountable for any adverse events, and so they tend to be protective of their prescriptions, and it is unlikely for the pharmacist to take such responsibility. This is, to a certain degree, similar to one of the findings of a study conducted in Ljubljana, Slovenia, where most physicians did not expect pharmacists to have the authority to interchange similar medications without consulting them first (12) . Most participants were fairly positive about the clinical pharmacists' participation in the daily medical rounds (average score = 3.195), and even more so about clinical pharmacists' availability for consultation (average score = 3.37), which can imply that, in most cases, shortage of interventions is not necessarily due to lack of interaction, and this is contrary to the results of another study conducted in Baghdad were 91.5% of the participants reported rarely interacting with pharmacists (7) .…”
Section: Discussionsupporting
confidence: 84%
“…In the visualization of the results for questions 14,15,16,17,32,35,36,41,44, and 46, we notice a substantial asymmetry of the reinforcement factors in an upwards direction. In the case of an increase of a value for these questions, the overall satisfaction value would increase.…”
Section: Tablementioning
confidence: 91%
“…Introduction of clinical pharmacy services was evaluated in [1,14,[23][24][25][26][27][28][29][30][31][32][33][34], but studies exploring the stakeholders' needs, expectations, and perceptions of clinical pharmacy services before their introduction are rare [35]. Only a few studies investigated the perception of clinical pharmacy services by all three professional groups involved-pharmacists, physicians and nurses [1,32,33].…”
Section: Related Workmentioning
confidence: 99%
“…They are out of the multidisciplinary team and can’t collaborate with the doctors and nurses to do their tasks ( Shanika et al, 2017 ). Many reasons seem to be behind this exclusion such as that physician’s fears of losing professional autonomy and independence ( Čufar et al, 2014 ); or physicians were found to be‘uncomfortable’ with pharmacists suggesting or recommending prescription medications to their patients ( Ables and Baughman, 2002 ) and the existence of a communication gap between pharmacists and physicians as reported in previous studies( Nesbit et al, 1995 , Sulick and Pathak, 1996 ). However, due to the lack of studies in Palestine, it is difficult to set how far clinical practice proceed in Palestine, and also lack of application of this service which leads to the lack of knowledge about it.…”
Section: Introductionmentioning
confidence: 95%